2019
DOI: 10.21276/ijcmr.2019.6.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Premature Presbyopia and its Risk Factors - A Hospital based Study

Abstract: Introduction: Presbyopia, a physiological insufficiency of accommodation, impairs the ability to perform near task. Considered as a disease of the forties, it reduces functional efficiency of the individual as well as the society since it affects the majority of working population. This study was an effort to evaluate the risk factors that can lead to its earlier onset. Purpose of the study was to evaluate the frequency of risk factors associated with premature presbyopia in a hospital-based study in Sundergar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Similarly, a study done in India reported prevalence as 9.8%. 8 This study is also in agreement with the systematic review and meta-analysis, 9 that showed the pooled prevalence of PROM was 9.2% among pregnant women in Ethiopia. In contrast, a multi-centric study in China, 10 showed a high prevalence of PROM to be 18.72%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, a study done in India reported prevalence as 9.8%. 8 This study is also in agreement with the systematic review and meta-analysis, 9 that showed the pooled prevalence of PROM was 9.2% among pregnant women in Ethiopia. In contrast, a multi-centric study in China, 10 showed a high prevalence of PROM to be 18.72%.…”
Section: Discussionsupporting
confidence: 90%
“…Most cases of PROM occurred in housewives aged 20 to 30 years old. 8 Similarly, the maximum cases belonged to the age group 25-29 years 25 (44.64%). A study conducted in Nigeria showed the previous history of PROM, history of preterm delivery, low socioeconomic status, and genitourinary infection were highly predictive of PROM.…”
Section: Discussionmentioning
confidence: 93%
“…It is important to note that there are a number of causes of accommodative anomalies encompassing a wide range of ocular and systemic conditions including trauma, inflammatory diseases, toxicity, vascular diseases, medications, environmental factors, iatrogenic causes, and more [40][41][42][43]. It is not the aim of this paper to cover all of these, and a complete eye examination and thorough patient history is always recommended.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, people of short stature were found to have earlier onset of presbyopia probably because they use shorter working distances which may require greater accommodation. 68 …”
Section: Discussionmentioning
confidence: 99%